2004
DOI: 10.1128/mcb.24.12.5565-5576.2004
|View full text |Cite
|
Sign up to set email alerts
|

Akt Mediates Ras Downregulation of RhoB, a Suppressor of Transformation, Invasion, and Metastasis

Abstract: Although recent evidence supports a tumor-suppressive role for the GTPase RhoB, little is known about its regulation by signal transduction pathways. Here we demonstrate that Ras downregulates RhoB expression by a phosphatidylinositol 3-kinase (PI3K)-and Akt-but not Mek-dependent mechanism. Furthermore, genetic and pharmacological blockade of PI3K/Akt results in upregulation of RhoB expression. We also provide evidence for the importance of the downregulation of RhoB in oncogenesis by demonstrating that RhoB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
143
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 37 publications
14
143
0
3
Order By: Relevance
“…These data indicate that aberrant activation of the PI3K pathway in glioblastoma represses RhoB expression primarily via activation of PKCi. Previously, it has been reported that in NIH3T3 mouse fibroblasts and human pancreatic cancer cells, PKB/Akt represses RhoB expression downstream of PI3K activation (Jiang et al, 2004). Inhibition of PKCi with myristoylated pseudosubstrate peptide increased RhoB levels without any effect on PKB/Akt phosphorylation (Figure 2c), showing that the role of PKCi in RhoB regulation is independent of PKB/Akt in glioblastoma cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…These data indicate that aberrant activation of the PI3K pathway in glioblastoma represses RhoB expression primarily via activation of PKCi. Previously, it has been reported that in NIH3T3 mouse fibroblasts and human pancreatic cancer cells, PKB/Akt represses RhoB expression downstream of PI3K activation (Jiang et al, 2004). Inhibition of PKCi with myristoylated pseudosubstrate peptide increased RhoB levels without any effect on PKB/Akt phosphorylation (Figure 2c), showing that the role of PKCi in RhoB regulation is independent of PKB/Akt in glioblastoma cells.…”
Section: Discussionmentioning
confidence: 63%
“…The stress-inducible fraction of RhoB expression is, in some cases, dependent on p38 MAP kinase (Gerhard et al, 2005). RhoB levels are also controlled by a second mechanism that involves the PI3K pathway (Jiang et al, 2004). We show here that PKCi is a downstream mediator in this pathway in glioblastoma cells, with both pharmacological inhibition of PKCi and depletion of PKCi using RNAi pointing to a role for PKCi in repressing RhoB expression.…”
Section: Discussionmentioning
confidence: 67%
“…12 Notably many oncogenes such as the epidermal growth factor receptor Ras, and Akt suppress the expression of RhoB in tumor cells. 9,13 Moreover, RhoB expression is dramatically decreased in numerous cell lines, including ovarian, lung or breast cancer, 14,15 as well as in brain, head and neck cancer where the tumors become more aggressive and highly invasive. 7,16,17 These studies suggest that RhoB could play a critical role in suppressing malignant transformation by blocking oncogenic and tumor survival pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was found that induction of RhoB resulted in either a prolonged transient block to DNA replication or apoptosis, upon treatment with DNA-damaging drugs (Fritz and Kaina, 2000). Recently, we demonstrated that oncogenes such as epidermal growth factor receptor (EGFR), ErbB2 and Ras suppress RhoB by a mechanism involving the phosphatidylinositol 3 0 -kinase (PI3K)/Akt pathway (Jiang et al, 2004a;Jiang et al, 2004b). Furthermore, we found that ectopic expression of RhoB suppresses oncogene-mediated malignant transformation, tumor survival, invasion and metastasis (Jiang et al, 2004a, b).…”
Section: Introductionmentioning
confidence: 99%